PENGARUH KECUKUPAN MODAL, UKURAN BANK, BIAYA OPERASIONAL DAN LIKUIDITAS TERHADAP KINERJA KEUANGAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Thaibah Thaibah; Faisal Faisal (Departemen Manajemen, 2020)
This study aims to determine the effect of capital adequacy, bank size, operating expenses, and liquidity in the financial performance of banks listed on the Indonesia Stock Exchange. This study uses panel data with 13 banks listed on the Indonesia Stock Exchange from 2013-2017. The analytical method used is multiple regression analysis with random effects models. The results show that: Capital adequacy has a positive and significant effect on financial performance. Bank size has a positive and insgnificant effect on financial performance. The operating expenses has a negative and significant effect on financial performance. Liquidity has a positive and insignificant effect on financial performance. Capital adequacy, bank size, operating expenses and liquidity simultaneously significant effect on the dependent variable, namely financial performance. Therefore, investors and the analysis can consider capital adequacy and operating expenses in financial performance.